(untitled) (Journal of the College of Education for Women, 2019)
This paper proposes a new method Object Detection in Skin Cancer Image, the minimumspanning tree Detection descriptor (MST). This ObjectDetection descriptor builds on thestructure of the minimum spanning tree constructed on the targettraining set of Skin CancerImages only. The Skin Cancer Image Detection of test objects relies on their distances to theclosest edge of thattree. Our experimentsshow that the Minimum Spanning Tree (MST) performsespecially well in case of Fogginessimage problems and in highNoisespaces for Skin CancerImage.The proposed method of Object Detection Skin Cancer Image wasimplemented and tested ondifferent Skin Cancer Images. We obtained very good results . The experiment showed that theproposedmethod obtained very good results but it requires more testing on different types of SkinCancer Images.